2005
DOI: 10.1111/j.1365-2419.2005.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Immature Steller sea lion (Eumetopias jubatus) dive activity in relation to habitat features of the eastern Aleutian Islands

Abstract: Current flow and bathymetry in the Aleutian Islands define unique habitats that influence prey distribution and foraging behaviour of top-level predators. We explored whether oceanographic features and bathymetry influenced the diving activity of 30 immature sea lions (ages 5-21 months) equipped with satellitelinked depth recorders in the eastern Aleutian Islands (EAI) during 2000-02. Sea surface temperature (SST) and chlorophyll a concentrations were obtained from remote sensing satellite imagery and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 43 publications
(103 reference statements)
6
56
2
1
Order By: Relevance
“…Fish at these sites were collected with a bottom trawl at depths ranging from 74 m to 160 m as part of a major survey of commercial fish distributions and abundance (Table 1). Sea lions typically forage within 16 km of these habitats (Fadely et al, 2005) and as deep as 288 m, although average diving depths are 26 m for pups and 63 m for yearlings (Loughlin et al, 2003. ).…”
Section: Methodsmentioning
confidence: 99%
“…Fish at these sites were collected with a bottom trawl at depths ranging from 74 m to 160 m as part of a major survey of commercial fish distributions and abundance (Table 1). Sea lions typically forage within 16 km of these habitats (Fadely et al, 2005) and as deep as 288 m, although average diving depths are 26 m for pups and 63 m for yearlings (Loughlin et al, 2003. ).…”
Section: Methodsmentioning
confidence: 99%
“…Assuming complete dependence, regional differences in pup blubber FA profiles would be a reflection of regional differences in the FA composition of adult female diets that were passed on to offspring through milk (Puppione et al 1996, Iverson et al 2001. However, recent studies of maternal attendance patterns (Trites & Porter 2002) and the dispersal and movement patterns of young SSLs (Loughlin et al 2003, RaumSuryan et al 2004, Fadely et al 2005 have suggested that some individuals may wean during the spring of :1n-11, 20:1n-11 and 20:5n-3; second function accounted for an additional 17.9% of variation and was most influenced by 16:1n-7, 18:1n-9 and 22:6n-3 their first year of life. If this is true, regional differences in the blubber FA profile of pups may also result from regional differences in prey consumption or in the timing of when pups begin to forage independently.…”
Section: Differences In Fa Profiles By Regionmentioning
confidence: 99%
“…In turn, under the bottom-up concept, patterns in the changes of oceanography and fish populations should be reflected in patterns of sea lion foraging ecology and abundance (Fadely et al 2005, Gende and Sigler 2006, Womble and Sigler 2006. The objective of this study, therefore, was to investigate these possible linkages by examining the spatial and temporal heterogeneity of sea surface temperature (SST) and chlorophyll a (chl a) associated with habitat use of Steller sea lions from four regions of the western DPS.…”
Section: Introductionmentioning
confidence: 99%